Perturbed Glucose Metabolism: Insights into Multiple Sclerosis Pathogenesis - Mathur, Deepali; López-Rodas, Gerardo; Casanova, Bonaventura; Marti, Maria Burgal (Frontiers in Neurology, 2014)
Multiple sclerosis (MS) is a complex debilitating disease of the central nervous system perceived to result from the autoimmune effect of T cells in damaging myelin sheath. However, the exact pathogenesis of the disease remains elusive. Initial studies describing the possibility of defective pyruvate metabolism in MS were performed in 1950s. The group observed elevated blood pyruvate level in both fasting and postprandial times in MS patients with relapse. Similarly, other investigators also reported increased fasting pyruvate level in this disease. These reports hint to a possible abnormality of pyruvate metabolism in MS patients. In addition, increase in levels of Krebs cycle acids like alpha-ketoglutarate in fasting and citrate after glucose intake in MS patients further strengthened the connection of disturbed pyruvate metabolism with MS progression. These studies led the investigators to explore the role of disturbed glucose metabolism in pathophysiological brain function. Under normal circumstances, complex molecules are metabolized into simpler molecules through their respective pathways. Differential expression of genes encoding enzymes of the glucose metabolic pathway in central nervous system (CNS) may result in neurological deficits. In this review article, we discussed the studies related to disturbed carbohydrate metabolism in MS and other neurodegenerative diseases. These observations open new perspectives for the understanding of metabolic dynamics in multiple sclerosis yet many puzzling aspects and critical questions need to be addressed. Much more research is required to fully unravel the disease mechanism, and a proper understanding of the disease could eventually lead to new treatments.